EXAMINING IRAQI HIGH SCHOOL STUDENTS’ PERCEPTIONS OF TEACHER FEEDBACK - Abbas, Alaa Abdul Adheem Abdul; Muslim, Afrah Mohammed; Enad, Aseel Ubaiss (PT. Antis International Publisher, 2025)
Objective: This study explores the attitudes of Iraqi high school students toward teacher feedback, focusing on how it influences their learning experiences and motivation. Method: Using a quantitative research design, data were collected from 52 male high school students in Najaf City, Iraq, through a structured questionnaire. Results: The findings reveal that students generally hold positive attitudes toward teacher feedback, perceiving it as beneficial and necessary for their academic development. A majority of students reported that teacher feedback increased their learning motivation and trusted their teachers' comments. However, some students expressed anxiety when receiving feedback and hesitated to ask questions, indicating a need for a more supportive feedback environment. Novelty: The study underscores the importance of teacher feedback in enhancing student learning while highlighting the need for strategies to reduce student anxiety and foster a more comfortable learning atmosphere.